2008
DOI: 10.1152/ajplung.00146.2007
|View full text |Cite
|
Sign up to set email alerts
|

Progressive dysfunction of nitric oxide synthase in a lamb model of chronically increased pulmonary blood flow: a role for oxidative stress

Abstract: SM. Progressive dysfunction of nitric oxide synthase in a lamb model of chronically increased pulmonary blood flow: a role for oxidative stress. Am J Physiol Lung Cell Mol Physiol 295: L756 -L766, 2008. First published August 29, 2008 doi:10.1152/ajplung.00146.2007.-Cardiac defects associated with increased pulmonary blood flow result in pulmonary vascular dysfunction that may relate to a decrease in bioavailable nitric oxide (NO). An 8-mm graft (shunt) was placed between the aorta and pulmonary artery in 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 50 publications
4
65
0
Order By: Relevance
“…Therefore we conclude that pulmonary capillary hydrostatic pressure in acute and chronic shunt lambs was elevated due to increased PBF. Additionally, because the lymph-to-plasma-protein ratio declined to a similar extent in the acute and chronic models, chronic exposure to increased PBF did not result in measurable losses in pulmonary capillary barrier function, despite previously described pulmonary vascular endothelial dysfunction (52).…”
Section: Discussionmentioning
confidence: 64%
“…Therefore we conclude that pulmonary capillary hydrostatic pressure in acute and chronic shunt lambs was elevated due to increased PBF. Additionally, because the lymph-to-plasma-protein ratio declined to a similar extent in the acute and chronic models, chronic exposure to increased PBF did not result in measurable losses in pulmonary capillary barrier function, despite previously described pulmonary vascular endothelial dysfunction (52).…”
Section: Discussionmentioning
confidence: 64%
“…To detect superoxide generation in peripheral lung tissue, EPR measurements were performed using the spin trap, 1-hydroxy-3-methoxycarbonyl-2,2,5,5-tetramethylpyrrolidine .HCl as already described (35,45). NOS-derived superoxide levels were determined by subtracting the superoxide values in the presence of the NOS inhibitor, ethylisothiourea (100 lM, ETU) from the superoxide values in the absence of ETU.…”
Section: Measurement Of Superoxide Levelsmentioning
confidence: 99%
“…Previous work has shown that eNOS-hsp90 interactions are progressively disrupted during the development of the endothelial dysfunction associated with increased PBF [75]. In addition to eNOS, hsp90 also chaperones other proteins involved in NO signaling.…”
Section: Hsp90 and No Signalingmentioning
confidence: 99%
“…Thus, the loss of ATP due to mitochondrial dysfunction attenuates hsp90 activity resulting in a "feed-forward" signaling cascade in which eNOS becomes ever more uncoupled leading to less NO-and more peroxynitrite-being produced driving pulmonary endothelial dysfunction [75] (Figure 3). In addition, the NO receptor, soluble Guanylyl Cyclase (sGC) is also found in a complex with hsp90 and Inhibition of hsp90 activity using geldanamycin stimulates it proteasomal degradation again via CHIP reducing the ability of the cell to produce cyclic guanosine monophosphate (cGMP) [77][78][79][80].…”
Section: Hsp90 and No Signalingmentioning
confidence: 99%
See 1 more Smart Citation